Lei Maria da Penha, análise do discurso e semiótica francesa: um ensaio sobre a adesão ao discurso da lei - Locher, Gabriela Barboza (Universidade Federal de São Carlos, 2018)
Under the assertion that the sphere Law shows itself like a space of discursive strategies, which there is a conflict of "truths" supported by arguments that are able to legitimize a certain power, the project in question is about to analyze the process of adherence to the discourse of Law 11.340 / 2006 (Maria da Penha Law) , which, disposes of mechanisms to restraint domestic and family violence against women, will build a corpus of analysis of the present investigation. Based on French discursive currents, we will seek to apprehend, from a historical and cultural point of view, the discursive practices and the relations of power, instigating the problematic in an interdisciplinary way, notably by imbricating the linguistic and legal in order to verify the effects of veracity and legitimacy that the legal text intends to pass, imbricated to a peculiar form of modalization of the masculine and feminine subjects. In this tuning, we will analyze the modality that circumvents the male figure, that is, what is determined to be, as well as the negative sanction due from possible lack of observance of the agreement proposed by the Maria da Penha Law, which may also materialize in the choleric allegory, which is capable of legal intervention. To do so, considering the updating modality attributed to women by the Judiciary, we will analyze beyond the socio-historical-cultural conditions that made possible the legal discourse Lei da Penha, central concepts such as discourse, subject, ethos, pathos and logos in order to understand the context that the woman is and how it reflects on the adherence to the discourse proposed in/by the Law under analysis.
Keywords: Discurso; Relações de poder; Semiótica francesa; Lei Maria da Penha; Discourse; Relationships of power; French semiotic; Maria da Penha Law; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA